The Influence Of Organizational Culture On Employee Performance At Siti Aisyah Islamic Hospital Madiun - Hapsari Anggrahenny; Suhadi Prayitno; Zaenal Abidin (International Journal of Health Literacy and Science, 2023)
Based on secondary data at Siti Aisyah Islamic Hospital Madiun, in 2017 there were employees who had sufficient value of 67,62%, in 2018 there were employees with sufficient value of 27,72%, and in 2019 there were employees with sufficient value of 38,46%. This study aims to determine the influence of organizational culture on employee performance at Siti Aisyah Islamic Hospital Madiun. This type of research is quantitative research with a crossectional approach. The population in this study is all employees at Siti Aisyah Islamic Hospital Madiun, which fits the criteria of 218 employees, with a sample of 100 respondents. Sampling technique using simple random sampling. The data used are primay data in the form of organizational culture questionnaires and employee performance, then it was analyzed using logistic regression tests. The result showed that most employees have a sufficient organizational culture with sufficient employee performance. The result of the logistic regression test show p value of 0,000>0,05 which show that there is a significant influence between organizational culture on employee performance, which is 45.9%. The suggestions from the researchers is that organizational culture can improve employee performance by paying attention to aggressiveness, innovation and risk taking, result orientation, and stability.